Does Supply Concentration Encourage Cooperation? Evidence from Airlines - Argyres, Nicholas; Gil, Ricard; Zanarone, Giorgio (Management Science, 2025)
One of a firm’s key strategic decisions is whether to concentrate its input purchases in a small number of suppliers versus spreading them among many suppliers. We propose that supplier concentration solves an interfirm free-riding problem: By internalizing externalities between suppliers, it incentivizes buyer-supplier cooperation. Guided by a simple theoretical model, we investigate this hypothesis on slot exchanges between major airlines and their outsourced regional airline partners during inclement weather, a setting where externalities between suppliers are ubiquitous. We find robust evidence that a regional airline engages in more frequent slot exchanges with its major airline partner when it operates a larger share of the major’s outsourced flights. We also find that this positive effect of concentration on mutual cooperation increases in the size of the externalities between regionals. Our results suggest that, in contrast with Porter’s classic five forces framework, supplier concentration can serve as a governance instrument for buyer-supplier collaborations. More broadly, our paper provides novel evidence on task concentration as a tool to solve free-riding problems in multiagent settings. This paper was accepted by Joshua Gans, business strategy. Funding: This paper received financial support from the Spanish Research Agency (MICIU/AEI) [Grants PID2022-136983NB-I00, MCIN/AEI /10.13039/501100011033]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.03455 .